The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1136/rapm-2019-100827
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound-guided erector spinae plane block and thoracic paravertebral block for postoperative analgesia after video-assisted thoracic surgery: a randomized controlled non-inferiority clinical trial

Abstract: Background and objectivesThe anesthetic characteristics of ultrasound-guided erector spinae plane block (ESPB) remain unclear. We compared the analgesic efficacies of ESPB and thoracic paravertebral block (TPVB) for analgesia after video-assisted thoracic surgery (VATS).MethodIn this prospective randomized non-inferiority trial, 88 patients undergoing VATS randomly received ESPB or TPVB. All patients received continuous infusion of 0.2% levobupivacaine (8 mL/hour) after injection of a 20 mL 0.2% levobupivacain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 22 publications
5
107
1
5
Order By: Relevance
“…There was no case of local anesthetic intoxation occurred in ESPB group in our study, after all, high volume and high concentration of ropivacaine increased the risk of local anesthesia toxicity [14,17].…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…There was no case of local anesthetic intoxation occurred in ESPB group in our study, after all, high volume and high concentration of ropivacaine increased the risk of local anesthesia toxicity [14,17].…”
Section: Discussionmentioning
confidence: 47%
“…This prospective randomized study showed that a single ESPB provided superior postoperative analgesia than the TPVB in patients undergoing video-assisted thoracoscopic lobectomy, which was different from recent studies. The other three studies all have proved that the analgesic effect of ESPB block is equal to or weaker than that of TPVB [14][15][16].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Erector spinae plane block (ESPB) is a novel inter-fascial plane block rst introduced by Forero et al in 2016 [6], providing wide-ranging analgesia in lung surgery [7][8][9], laparoscopy [10], mastectomy [11] and pediatric surgery [12,13]. The proposed mechanism of ESPB is that distribution of local anesthetic solution spreads into the paravertebral space and epidural space [14], which then blocks the dorsal, ventral, and tra c branches of spinal nerve.…”
Section: Methodsmentioning
confidence: 99%
“…Paravertebral block is deemed as a premium alternative to epidural block, has been used for many years in various kinds of surgery due to its de nite analgesia [31]. Most of the recent studies have compared ESPB with intravenous analgesia, however, there is still lack of study comparing ESPB with TPVB except Taketa and colleagues' work [32]. What's more, the mechanism by which ESPB works through paravertebral space remains con icting [15].…”
Section: Disscussionmentioning
confidence: 99%